2015
DOI: 10.1242/dev.126649
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic microRNA-101a and Fosab expression controls zebrafish heart regeneration

Abstract: Cardiovascular disease is the leading cause of morbidity and mortality in the Western world owing to the limited regenerative capacity of the mammalian cardiovascular system. In lieu of new muscle synthesis, the human heart replaces necrotic tissue with deposition of a noncontractile scar. By contrast, the adult zebrafish is endowed with a remarkable regenerative capacity, capable of de novo cardiomyocyte (CM) creation and scar tissue removal when challenged with an acute injury. In these studies, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 56 publications
3
52
0
Order By: Relevance
“…6J). Both genes were shown to be expressed in dedifferentiated, proliferating cardiomyocytes in fish (Aguirre et al, 2014;Beauchemin et al, 2015), suggesting that changes in mycb and fosab expression might be associated with the reduction in cardiomyocyte proliferation in Notch-abrogated hearts. RNA-seq analysis indicated an upregulation of genes encoding sarcomere assembly and function proteins (Fig.…”
Section: Notch Signalling Regulates Cardiomyocyte Proliferation and Dmentioning
confidence: 99%
“…6J). Both genes were shown to be expressed in dedifferentiated, proliferating cardiomyocytes in fish (Aguirre et al, 2014;Beauchemin et al, 2015), suggesting that changes in mycb and fosab expression might be associated with the reduction in cardiomyocyte proliferation in Notch-abrogated hearts. RNA-seq analysis indicated an upregulation of genes encoding sarcomere assembly and function proteins (Fig.…”
Section: Notch Signalling Regulates Cardiomyocyte Proliferation and Dmentioning
confidence: 99%
“…The only factor known to be involved in this process so far is a microRNA (miR-101a), whose expression is downregulated shortly after heart injury, which appears to be necessary to allow cardiomyocyte cell cycle re-entry to occur. Expression is upregulated again at 7 days post injury and suppression of miR-101a activity during the latter period results in defects in scar removal [64 ]. Both effects of miR-101a appear to be mediated by its suppression of the transcription factor fos, which is required for cardiomyocyte proliferation, yet acts as an inhibitor of scar tissue clearance [64 ].…”
Section: Regeneration-specific Signaling Functionsmentioning
confidence: 99%
“…Expression is upregulated again at 7 days post injury and suppression of miR-101a activity during the latter period results in defects in scar removal [64 ]. Both effects of miR-101a appear to be mediated by its suppression of the transcription factor fos, which is required for cardiomyocyte proliferation, yet acts as an inhibitor of scar tissue clearance [64 ].…”
Section: Regeneration-specific Signaling Functionsmentioning
confidence: 99%
“…This now widely used method demonstrated that even after significant injury, such as surgical removal of 20% of the ventricle; the heart has the ability to fully regenerate (Poss et al, 2002). After resection, a fibrin clot seals the wound, and collagen is deposited (Poss et al, 2002; Beauchemin et al, 2015). However, over the course of 1–2 months, the scar is cleared and the myocardial layer is regenerated (Poss et al, 2002; Raya et al, 2003).…”
Section: Zebrafish Model For Heart Regeneration Researchmentioning
confidence: 99%
“…Compared with extrinsic signals, our knowledge about intrinsic programs that regulate cardiomyocyte proliferation is limited to several microRNAs (Yin et al, 2012; Beauchemin et al, 2015), and cardiac transcription factors gata4 (Kikuchi et al, 2010) and hand2 (Schindler et al, 2014). It is still largely unknown how these intrinsic programs are linked to extrinsic signals, however, a recent study showed a functional link between extrinsic (Nrg1) and intrinsic ( gata4 ) programs.…”
Section: Major Cell Types and Their Contributions To Heart Regenerationmentioning
confidence: 99%